Hydrogen-powered horizons: Transformative technologies in clean energy generation, distribution, and storage for sustainable innovation - Sikiru S. (Elsevier Ltd, 2025)
The advancement of clean energy and the long-term progress in the energy industry hinge on the crucial processes of generating, transporting, and storing hydrogen. As a versatile energy source, hydrogen can be produced through various renewable sources such as biomass, solar energy, wind, and water. This review article examines the impact of hydrogen on energy storage and explores various methods for hydrogen production from both fossil fuels and renewable energy sources. The technological, economic, and environmental implications of these methods are considered, with a specific focus on hydrogen production from low-carbon sources. This review explores hydrogen's potential as an energy storage solution, comparing fossil fuels and renewable sources. It evaluates the technological, economic, and environmental implications of each method and highlights its benefits and drawbacks. Hydrogen has potential applications in transportation, manufacturing, and power generation but faces challenges in widespread use. The review emphasizes the need for ongoing research, advancement, and cross-sector cooperation to fully harness hydrogen's eco-friendly and low-carbon potential. The review outlines the potential benefits of hydrogen energy, such as its capacity to reduce carbon emissions in different industries, while also discussing the obstacles hindering its widespread use. The research recommend a detail perspective on the future of hydrogen energy, underscoring the importance of finding a balance between its advantages and challenges to effectively incorporate it into the world's energy system. It emphasizes the significance of ongoing research, advancement, and cross-sector cooperation to fully exploit hydrogen's potential as an eco-friendly and low-carbon energy source. ? 2023 Hydrogen Energy Publications LLC